Identification of S419 on human serum albumin as a novel biomarker for sarin and cyclosarin exposure. (27th February 2020) - Fu, Feiyan; Liu, Haibo; Lu, Xiaogang; Zhang, Ruihua; Li, Liqin; Gao, Runli; Xie, Jianwei; Wang, Hongmei; Pei, Chengxin
Abstract : Rationale: Organophosphorus nerve agents are highly toxic because they inhibit acetylcholinesterase activity, thereby causing a series of symptomatic poisoning. Upon entering the body, nerve agents bind active amino acid residues to form phosphonylated adducts. A potentially beneficial method for specific verification of exposure of nerve agents is based on albumin adducts, which have a half‐life of 18 days. This appears to be more effective than the fluoride reactivation method, based on acetylcholinesterase. Methods: After the exposure of human serum albumin to nine nerve agents, human serum albumin was denatured, reduced, alkylated and digested with trypsin according to standard mass spectrometry‐based proteomics procedures. The phosphonylated peptides of human serum albumin were identified using positive ion electrospray ionization with a quadrupole orbitrap mass spectrometer. Results: The peptide KVPQVSTPTLVESR showed a good mass spectrometric response to the nine nerve agents. The tendency of sarin and cyclosarin was to bind to S419 on the peptide, while the other nerve agents (tabun, soman and V‐type nerve agents) were shown to bind more readily to K414 on the peptide. Conclusions: This research revealed a new site, S419, of the tryptic peptide KVPQVSTPTLVEVSR on human albumin to be a valuable biomarker for sarin/cyclosarin exposure, helping to further distinguish sarin and cyclosarin poisoning from that of other nerve agents and providing an important tool for the identification of sarin or cyclosarin in terrorist attacks.